Glorification of the Past as a Political Tool: Ottoman history in contemporary Turkish politics. Issue 4 (2nd October 2018) - Uzer, Umut
ABSTRACT: Turkey's radical transformation of state and society under Mustafa Kemal Atatürk's republican rule (1923–1938) has been subject to a gradual revision under the Justice and Development Party (AKP) government since 2002. The creation of a new state identity has been buttressed with Islamic and Ottoman discourses, which entail a reinterpretation of Ottoman history. This study analyzes the changes in modern Turkey in the last sixteen years within the context of the use of the Ottoman past in the formation of a new national identity by the AKP government.